Heat Transfer Characteristics of Paraffin in Staggered Fins Heat Exchanger for the Cooling Process to Room Cooling Applications. Issue 1 (June 2020) - Irsyad, M; Akmal, M; Susila, M D; Amrizal,; Amrul,
Abstract: The night air temperature which is below or equal to the temperature of human thermal comfort is very potential to be used to help reduce the thermal load of the room. This utilization can help minimize the electrical energy consumption of air conditioning systems. Phase change material (PCM) can be used to utilize the potential of cold air at night as latent heat thermal energy storage (LHTES). One model of the application of PCM is the heat exchanger. PCM fills one part of the heat exchanger. The characteristics of heat transfer need to be known so that it can know the cooling rate and the time required in the process. The variable used in this study is the inlet air velocity. In this research, a staggered fins-type heat exchanger which contains PCM with paraffin material is used in the cooling process. The results showed that an increase in speed would accelerate the cooling rate. At a velocity of 3 m.s −1, the average cooling rate of the PCM mass unity was 6.4 °C.hr'.kg −1 . With this rate of cooling, the potential for cold night air for about two to three hours can be utilized for the PCM freezing process.